Who is giving these days? On the Role of Religiosity in Giving - Abreu, M. E.; Laureano, Raul M. S.; Vinhas da Silva, Rui (ESA Sociology of Religion Research Network Conference: Religion in the Public Domain, 2014)
Religion is nowadays increasingly conceived on the private sphere of the individual on its money usage decisions vis-a-vis with the institutionalized domain. This accounts also for the giving decisions a donor has to take. What is more, religiosity and religious affiliation are major dimensions in the realm of religion (Campbell and Coles, 1973). Religious affiliation can be defined as the adherence of individuals to a particular religious group, within the public sphere of denominations (Essoo & Dibb, 2004); whereas religiosity can be seen as the degree to which beliefs and religious values are practiced and experienced by a person (Tienen, Scheepers, Reitsma, & Schilderman, 2010). So, the aim of this study is to uncover the influence of a donor’s “experience of religion” on its donations practices. A large scale survey was online between February and April 2010 in Portugal, via five types of charities, demonstrating the options of 602 donors on fundraising decisions, regarding topics as religiosity, religious affiliation, frequency of donations, the type of organization being helped, and the level of donations. Bivariate techniques were applied for further analysis. This study demonstrates that non religious people, but displacing a high level of religiosity, also tend to give high donations and choose both religious as secular organizations for their donations. These results can play a vital role for organizations while appealing for fundraising purposes. Moreover, although limited to the Portuguese context, they launch a new debate for the impact religion may have on donations.